Analisis Struktur dan Nilai Geguritan Patibrata - Istri Anom, Anak Agung; Dhika Dharma Putri, Anak Agung Istri (Program Studi Filsafat Agama Hindu IAHN Gde Pudja Mataram, 2025)
Geguritan is a classical Balinese literary form that continues to captivate literature enthusiasts. Geguritan Patibrata conveys profound Hindu religious teachings, particularly significant for Hindu women in fulfilling their swadharma (sacred duty) in society. This study aims to explore the structure and values embedded in Geguritan Patibrata. The research methodology consists of manuscript inventory and literature review for data collection, while translation and descriptive methods are applied for analysis. Structural analysis reveals three core elements: theme, plot, and characterization. The central theme is a wife's loyalty to her husband, reflecting the concept of patibrata. The plot follows a classical structure: (1) The exposition introduces the main character, Dhyah Sunyawati. (2) The complication emerges as Wang Bhang Mahacitta falls in love with Dhyah Nawang Sasih, intending to marry her. (3) The resolution shows Dhyah Sunyawati, discovering her husband’s sorrow and, out of selflessness, granting him permission to marry Dhyah Nawang Sasih. Dhyah Sunyawati is the protagonist, supported by characters including Wang Bhang Mahacitta, Dhyah Nawang Sasih, Dhang Hyang Mahadisara, Wang Bhang Dwiyajñana, Dhyah Dwiajñani, Dhang Hyang Lingga Pranawa, and Maharsi Sri Winddhu. The work conveys philosophical values (Widhi Tattwa, Atma Tattwa, Karma Phala Tattwa, Punarbhawa Tattwa), ethical values (faithfulness, politeness, sincerity), and aesthetic values through poetic depictions of nature in the hermitage.